Understanding & using educational theories - Aubrey, Karl; Riley, Alison (London SAGE, 2019)
Provides an overview of a selection of the influential thinkers on education, whose writing has helped in shaping our views on teaching and learning.
1. John Dewey: A democratic notion of learning -- 2. Maria Montessori: Liberating the child -- 3. Jean Piaget: Understanding the mind of the child -- 4. Lev Vygotsky: An early social constructivist viewpoint -- 5. B.F. Skinner: The father of operant conditioning -- 6. Benjamin Bloom: Learning through taxonomies -- 7. Malcolm S. Knowles: Contextualising adult learning -- 8. Jerome Bruner: An evolution of learning theories -- 9. Urie Bronfenbrenner: The ecology of human development -- 10. Paulo Freire: Oppression, freedom and critical approaches to education -- 11. Donald Schön: Reflection and learning -- 12. David Kolb: Experiential Learning Theory -- 13. Jean Lave and Etienne Wenger: Socially situated learning and communities of practice -- 14. Guy Claxton: Learning power.
Includes bibliographical references and index.
Keywords: Education -- Philosophy; Critical pedagogy